Review of Ihor Nemchynov’s monograph “Малининъ/Malinin: Reconstruction of the “Lost Biography” of Kyiv Professor” – Vinnytsia: Baranovska T. P., 2019, 194 p. - Mozghova, Nataliia (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2020)
Ihor Nemchynov's monograph is the first attempt to bring back, after more than a hundred years of absolute oblivion, the name of professor Vasyl Mykolayovych Malinin (1849-1927), author of literary treatise on Elder Philophey, to the wide public and scientific community. To me, as a researcher of such a unique cultural and educational center of Kyiv of the XIX century. as the Kyiv Theological Academy (KTA), it is especially pleasing to note that the work of the author stands out for a careful, caring and respectful attitude both to the study of the professor's personal life and to the reconstruction of the wide panorama of socio-political and cultural-educational processes that took place in the middle of the XIXth century both in the territory of the Russian Empire in general and in Kyiv in particular.